Ketimpangan Kontrak Baku dalam Platform Digital: Analisis Hukum terhadap Perlindungan Pelaku Usaha Mitra berdasarkan Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Ananda, Salsabila Putri (LITERATUS, 2026)
The rapid development of platform-based digital economy has significantly transformed legal relationships between digital platform companies and their business partners, particularly through the use of standard form contracts drafted unilaterally. This study aims to analyze the inequality of standard contracts in digital platforms and to examine the relevance of legal protection for business partners based on Law Number 8 of 1999 concerning Consumer Protection. This research applies a qualitative approach using normative juridical methods, focusing on the analysis of statutory regulations, legal doctrines, and contractual practices in the digital economy. The results indicate that standard form contracts in digital platforms create an unequal bargaining position between platforms and their partners, reflected in the presence of exemption clauses, transfer of operational risks, and unilateral authority to modify policies and terminate partnerships. Such conditions potentially contradict the principles of justice, fairness, and good faith in contract law. Furthermore, the position of business partners substantively reflects characteristics of a weaker party, thereby justifying the need for legal protection. Through an extensive interpretation, the provisions of Consumer Protection Law, particularly Article 18, can be applied as a legal basis to invalidate unfair standard clauses. Therefore, stronger regulatory frameworks and government supervision are required to establish a more equitable, balanced, and sustainable digital business envi